A sustainable and green process based on froth flotation for effective recovery of combustibles from coking coal fines. Issue 7 (3rd July 2022) - Wang, Junyu; Park, Hangil; Ng, Chun Yong; Wang, Liguang
ABSTRACT: This paper reports experimental results for the flotation of a coking coal sample in highly saline water free of any organic chemicals using an oscillatory air supply. The results are compared with those obtained using a conventional steady air supply. The experiments were conducted with 0.5 M NaCl solution using a laboratory-scale flotation column equipped with a 50 µm pore-sized sparger. The oscillatory air supply was separately generated via two different devices: a fluidic oscillator and a solenoid valve. At a given air flowrate, conversion of the air supply pattern from steady to oscillatory via either of these devices significantly improved the combustible recovery from 44% to over 90%, and there was little difference in the flotation performance achieved using these two oscillatory air generation devices. The enhanced recovery of combustibles can be attributed to reduced bubble size and enhanced bubble surface area flux.